Caregiver Reported Quality of End-of-Life Care of Adolescent and Young Adult Decedents With Cancer. Issue 2 (April 2022) - Currie, Erin R.; Johnston, Emily E.; Bakitas, Marie; Roeland, Eric; Lindley, Lisa C; Gilbertson-White, Stephanie; Mack, Jennifer
Background: The quality of palliative and end-of-life (EOL) care for adolescents and young adults (AYAs) with cancer remains largely unknown.Objective: To describe caregivers of AYA cancer decedents perspectives' on EOL care quality related to EOL care communication.Design: Cross-sectional observational study.Setting/Subjects: Caregivers (n = 35) of AYAs who died from a cancer diagnosis from 2013-2016 were recruited from 3 U.S. academic medical centers.Measurements: Caregiver participants completed structured surveys (FAMCARE scale and the Toolkit After-Death Bereaved Family Member Interview) by telephone to gather perceptions of quality of EOL care of their AYA cancer decedents.Results: Caregivers reported unmet needs regarding preparation for the time of death (50%), the dying process (45%) and unmet spiritual/ religious needs (38%). Lowest quality of EOL care scores related to communication and emotional support.Conclusions: Our findings call for special focus on providing information about what to expect during the dying process and adequately addressing spiritual and religious preferences during EOL care for AYAs.